Reconciling Evolution and Biblical Literalism: A Proposed Research Program. Issue 2 (2nd April 2016) - Loke, Andrew Ter Ern
ABSTRACT: Many leading Christian thinkers today accept evolution, but others worry that certain incompatibilities with Biblical doctrines concerning Adam remain. In Should Christians Embrace Evolution, theologian Wayne Grudem succinctly summarizes their main objections when he claims that adopting evolution leads to eight positions contrary to the teaching of the Bible. In response, I show that, regardless of whether evolution occurred or not, there is no incompatibility even when a consistently literal reading of the relevant Biblical texts is maintained.